The FDA's sentinel initiative—A comprehensive approach to medical product surveillance. Issue 3 (12th January 2016) - Ball, R; Robb, M; Anderson, SA; Dal Pan, G
Abstract : In May 2008, the Department of Health and Human Services announced the launch of the Sentinel Initiative by the US Food and Drug Administration (FDA) to create the Sentinel System, a national electronic system for medical product safety surveillance.1 2 This system complements existing FDA surveillance capabilities that track adverse events reported after the use of FDA regulated products by allowing the FDA to proactively assess the safety of these products.